Education for Healthcare Providers: Impact of Academic Detailing on Reducing Misinformation and Strengthening Influenza Vaccine Recommendations - Kimberly C. McKeirnan; Megan E. Giruzzi; Damianne C. Brand; Nick R. Giruzzi; Kavya Vaitla; Juliet Dang (Pharmacy)
Background: Recommendations from a trusted healthcare provider have been shown to be the most effective intervention for encouraging patients to be vaccinated. However, providers have reported feeling less prepared to address vaccination questions and having less time to discuss vaccines with patients than before the COVID-19 pandemic. Providers may benefit from a brief update about the available influenza vaccines and vaccination guidelines. Academic detailing is an evidence-based approach for preparing healthcare providers to discuss getting vaccinated with patients. Methods: An academic detailing presentation was developed using influenza statistics, vaccination recommendations, and recent local and national immunization rate data. Academic detailing was conducted with physicians and community pharmacy personnel in Yakima County, Washington, between November 2023 and January 2024. Yakima County is designated as a medically underserved area due to a lack of providers. A pre-detailing survey was conducted to evaluate participant knowledge of current ACIP recommendations and gather opinions about local resident vaccination barriers. A post-detailing survey was conducted to gather participants’ opinions about the value of detailing. Results: Prior to the training, 73% of providers believed it was important to discuss influenza vaccination with patients, but only 52% felt confident in combating misinformation. Healthcare providers believed misinformation and vaccine hesitancy are the most common barriers for Yakima County patients, but recent survey results showed that online scheduling systems, long wait times, and limited appointment hours were the predominant issues reported locally. Two out of 12 community pharmacy personnel and zero resident physicians correctly named all three preferentially recommended influenza vaccines for patients 65 years and older. Overall, 96% of detailing participants reported that the session was valuable, 87% believed it would help them combat vaccine misinformation, and 65% reported planning to have more conversations with patients about influenza vaccination after participating. Conclusion: Physicians and community pharmacy immunizers found the influenza vaccines academic detailing to be valuable. Staying up to date on vaccination guidelines can prepare providers to be confident in having informed conversations with patients about getting vaccinated.